2015
DOI: 10.1200/jco.2014.57.6652
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Cause of Death in Patients Diagnosed With Myeloproliferative Neoplasms in Sweden Between 1973 and 2005: A Population-Based Study

Abstract: Patients with MPN had an overall higher mortality rate than that of matched controls, primarily because of hematologic malignancy, infections, and vascular events in younger patients. Evidently, there is still a need for effective disease-modifying agents to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 44 publications
2
93
1
1
Order By: Relevance
“…Especially during the earlier decades, a substantial degree of underreporting existed in this cohort. Nevertheless, this cohort has been very valuable and has shown an increased risk for first‐degree relatives to develop MPN, described which therapies are connected with an increased risk of AML transformation in MPN, and causes of death in MPN …”
Section: Discussionmentioning
confidence: 99%
“…Especially during the earlier decades, a substantial degree of underreporting existed in this cohort. Nevertheless, this cohort has been very valuable and has shown an increased risk for first‐degree relatives to develop MPN, described which therapies are connected with an increased risk of AML transformation in MPN, and causes of death in MPN …”
Section: Discussionmentioning
confidence: 99%
“…The frequency of arterial (16%) and venous (7.4%) thrombosis in 1818 patients diagnosed in the last decade was lower than in previous historical cohorts, including the ECLAP study (27% and 11%, respectively), 55,56 but was similar to the contemporary Cyto-PV study (arterial 17%, venous 12%) and the Swedish registry. 57 However, it is remarkable that while a reduction of thromboses from 4.01 to 2.93 per 100 patient-years was seen in the "high-risk" category, the rate of vascular events was unchanged in the "low-risk" category (2.03 vs. 2.24), thereby suggesting some under-treatment of these conventionally-defined low-risk subjects. 58 This is supported by the unexpected higher rate of thrombosis in young patients (age < 40 years) with masked PV compared with overt PV (3.01 vs. 1.99 per 100 patient-years, respectively).…”
Section: Risk Stratificationmentioning
confidence: 98%
“…[14][15][16] One recent retrospective study of Swedish patients with myeloproliferative neoplasms (MPNs) found a greater risk of death from cardiovascular disease for patients with MPN than for matched controls (hazard ratio [HR], 1.5-8.8, depending on the age group). 20 To the best of our knowledge, no similar studies specifically analyzing CML have been published. Because the VE rates have not been analyzed in a general CML population (in contrast to non-CML patients), it is not known what proportion of VEs will result from TKI therapy or from underlying CML disease compared with what could be expected in a demographically similar, non-CML population.…”
Section: Introductionmentioning
confidence: 97%